Movhera Baixo Sabor: Exploration Phase - Cliff-nesting species: Breeding sites [2021-2023] ... - Cabral, João Alexandre; Jesus, Joaquim; Travassos, Paulo; Carvalho, Diogo; Gomes, Carla; Brás, Luís; Barros, Paulo (Movhera - Hidroelétricas do Norte, S.A., 2024)
The dataset contains records of nests of cliff-nesting species of high conservation priority, namely birds of prey and Black Stork (Ciconia ciconia) (Aves) collected in the lower valley of River Sabor (NE Portugal), in the scope of the long-term Ecological Monitoring Program (PME) of the Baixo Sabor Hydroelectric Dams (AHBS), promoted by EDP – Energias de Portugal, S.A., subsequently (2021) transferred to Movhera – Hidroelétricas do Norte, S.A. This dataset includes results of nest surveys carried out at and around the area affected by the dam, from January 2021 to July 2023. Data consists of observations of all nests of the target species found in the study area, which were followed throughout the reproduction period (January-July) of each year. The records include the number of young produced by each couple in each year, if available. The target species were Golden Eagle (Aquila chrysaetos), Bonelli's Eagle (Aquila fasciata), Griffon (Gyps fulvus), Egyptian Vulture (Neophron percnopterus), Peregrine Falcon ...